2022
DOI: 10.1038/s41598-022-06007-y
|View full text |Cite
|
Sign up to set email alerts
|

Real life experience with the wearable cardioverter-defibrillator in an international multicenter Registry

Abstract: Patients at high risk for sudden cardiac death (SCD) may benefit from wearable cardioverter defibrillators (WCD) by avoiding immediate implantable cardioverter defibrillator (ICD) implantation. Different factors play an important role including patient selection, compliance and optimal drug treatment. We aimed to present real world data from 4 centers from Germany and Switzerland. Between 04/2012 and 03/2019, 708 patients were included in this registry. Patients were followed up over a mean time of 28 ± 35.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
6
2
Order By: Relevance
“…In our tertile age analysis, adherence was observed more in 73–91 years old group as compared to 14–51 years old group. In this regard, the WEARIT‐France study and another study showed that younger age was associated with a lower compliance 22,23 . However, our data showed that adherence with WCD use was not sex specific.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In our tertile age analysis, adherence was observed more in 73–91 years old group as compared to 14–51 years old group. In this regard, the WEARIT‐France study and another study showed that younger age was associated with a lower compliance 22,23 . However, our data showed that adherence with WCD use was not sex specific.…”
Section: Discussioncontrasting
confidence: 52%
“…In this regard, the WEARIT-France study and another study showed that younger age was associated with a lower compliance. 22,23 However, our data showed that adherence with WCD use was not sex specific.…”
Section: Adherencecontrasting
confidence: 58%
“…In most cases, SCD is triggered by ventricular arrhythmias ( 38 ). Implantable cardioverter defibrillator (ICD) and wearable cardioverter defibrillator (WCD) are recommended for the prevention of SCD in selected populations ( 39 , 40 ). Our meta-analysis showed that there was a 21% reduction in the risk of SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications reported that by using a wearable cardioverter defibrillator (WCD), a permanent ICD could be avoided in a significant part of patients 4–6 . The Vest trial investigated the benefit of WCD in 1524 patients, who suffered a myocardial infarction and developed a reduced LVEF; 778 patients were randomized for a WCD, and 746 patients did not receive a WCD.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several publications reported that by using a wearable cardioverter defibrillator (WCD), a permanent ICD could be avoided in a significant part of patients. [4][5][6] The Vest trial investigated the benefit of WCD in 1524 patients, who suffered a myocardial infarction and developed a reduced LVEF; 778 patients were randomized for a WCD, and 746 patients did not receive a WCD. Despite treatment with WCD, the arrhythmic death was not significantly different (1.6% vs. 2.8%, p = .18), however, the all-cause mortality was significantly reduced (3.1% vs. 4.9%, p = .04).…”
Section: Introductionmentioning
confidence: 99%